Commodification, Viewership and a For-anyone-as-someone "Special" Structure - Johnson, RJK (The Popular Culture Association of Australia and New Zealand (PopCAANZ), 2015)
Paddy Scannell’s analysis of broadcasting as a ‘for-anyone-assomeone structure’ (2000: 5) remains a key theoretical delineation of the role radio, television (and, now, digital media) play in everyday life. In essence, the development and deployment of the ‘for-anyone-assomeone structure’ allowed the speech patterns of broadcasting to gain and retain relevance to individual listeners and viewers within a mass context. As recent research has demonstrated (Ekstrom et al 2013), Scannell’s model remains relevant to contemporary mediascapes, particularly in relation to formats, like news, where broadcasting “speaks” directly to listeners and viewers. There is, however, another level on which broadcasting speaks its listeners and viewers – the wider, systemic level set by the rules, standards and norms within which individual networks, stations, and people “make” broadcasting happen. From this perspective, one can note that Scannell developed his model within the British context where commercial messages, where they are present, are relatively limited in reach and scope by regulation and professional practice. This paper will argue that a different category of listener and viewer exists within highly commercialised media environments like New Zealand’s – the commodified listener / viewer, who is spoken to by her broadcasting system as “someone special”.
Keywords: Care structure; For-anyone-as-someone; Commercial television; Promotional culture